A Bottom-Up Assessment of Crop-Sector Greenhouse Gas Emissions and Mitigation Potential in Kenya - Kakai, L.F.; Noufa, C.K.; Sapkota, T.B.; Corbeels, M.; Choptiany, J.M.H. (International Institute of Tropical Agriculture, 2025)
Agriculture is a major contributor to Kenya’s national greenhouse gas (GHG) emissions, yet existing estimates are largely derived from national-level inventories that rely on aggregated activity data and default emission factors, limiting their ability to capture spatial heterogeneity and management-specific mitigation opportunities. This study presents the first county-level, crop-specific assessment of GHG emissions from Kenya’s crop sector using a bottom-up analytical framework. By integrating subnational production data, soil and climate information, and detailed management practices, we generate spatially explicit estimates for fourteen major crops, with results reported for seven key food and industrial crops. Emissions of CO₂, CH₄, and N₂O were quantified at the farm-gate level using the CCAFS Mitigation Options Tool, and mitigation potentials were evaluated through a set of counterfactual management scenarios relative to a business-as-usual baseline. The results show that national crop-related emissions increased from approximately 2.8 Mt CO₂e in 2013 to over 4.0 Mt CO₂e in 2020, before a slight decline in 2021. Emissions are highly concentrated in a small number of high-production counties, reflecting both scale and management intensity. Maize dominates the national emissions profile (39–52%), driven primarily by its extensive cultivated area, while rice exhibits the highest per-hectare emission intensities, particularly in irrigated systems. Mitigation scenario analysis indicates that improvements in nitrogen-use efficiency consistently deliver larger reductions than single-practice interventions, with combined management packages yielding the greatest mitigation potential. These findings underscore the importance of spatially differentiated systems-based mitigation strategies. By linking subnational emissions accounting with policy-relevant scenarios, this study provides a framework for more targeted, evidence-based implementation of Kenya’s climate commitments under the NDC, NCCAP, ASTGS, and CSA Strategy, while safeguarding productivity and food security.